HOW SELF-CONTROL IMPACT’S ON HAPPINESS AND SATISFACTION WITH LIFE WITH MODERATING ROLE OF LOCUS OF CONTROL - Hussain, Sajid; Baqir, Muhammad; Islam, K. M. Anwarul; Asif, Samra (American Economic & Social Review, 2020)
Self-control is by all explanations a basic worth affecting how others see us and how we see ourselves. The basic aim of the study is to elaborate the vice versa relationship among the factor to test whether certain psychological variable which increases the satisfaction with life. Component of happiness with the influence of locus of control is correlated with each other which is we find in this research. The participants in the study were 307 students of the different institutes who fill questionnaires through snowball sampling. This had a significant huge relationship with the locus of control. In this study, we use a different technique to find the relationship with data. Firstly we test the reliability of the questionnaire which is used by the different researcher in their research article after this we find the correlation which shows the positive result among the variable. Subsequently, MANOVA and other test were applied in this research to emphasize how self-control plays a major role to enhance the level of happiness which discovered the true meaning of satisfaction. This study recommended that if students and people are good at self-control elements in different situations then they will be happier and satisfied with their life. Moreover, the investigation uncovered that self-control has emphatically corresponded with Happiness, regularity feeling, and satisfaction with life. Research on happiness has caused it conceivable to better comprehend human behaviour in different parts of life.